2020
DOI: 10.1029/2020wr027340
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Hydrologic Model Process Connectivity at the Continental Scale Through an Information Theory Approach

Abstract: Exploring water fluxes between hydrological model (HM) components is essential to assess and improve model realism. Many classical metrics for HM diagnosis rely solely on streamflow and hence provide limited insights into model performance across processes. This study applies an information theory measure known as "transfer entropy" (TE) to systematically quantify the transfer of information among major HM components. To test and demonstrate the benefits of TE, we use the Framework for Understanding Structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 95 publications
1
7
0
Order By: Relevance
“…The predictor with the largest influence is the fraction of precipitation as snow f S , which is used as a predictor in eight of the nine relationships. This is in close agreement with the findings by Konapala et al 64 , who also identified the fraction of snow as a key characteristic to explain runoff signals in their study based on an information theory approach. The four processes that benefit from adding a second predictor are Quickflow, Convolution of Surface Runoff, Rain-Snow Partitioning and Precipitation Correction.…”
Section: Resultssupporting
confidence: 93%
“…The predictor with the largest influence is the fraction of precipitation as snow f S , which is used as a predictor in eight of the nine relationships. This is in close agreement with the findings by Konapala et al 64 , who also identified the fraction of snow as a key characteristic to explain runoff signals in their study based on an information theory approach. The four processes that benefit from adding a second predictor are Quickflow, Convolution of Surface Runoff, Rain-Snow Partitioning and Precipitation Correction.…”
Section: Resultssupporting
confidence: 93%
“…The hydrological models and mechanisms for hypothesis testing are generated using the FUSE, a multihypothesis hydrological modeling system designed to facilitate work on model representation and improvement (e.g., Clark et al, 2008;2011a;Konapala et al, 2020). The FUSE mechanisms are represented by components of existing models, namely, PRMS, SACRAMENTO, TOPMODEL, and ARNO/VIC.…”
Section: Modeling Framework For Hypothesizing Hydrological Mechanisms...mentioning
confidence: 99%
“…The choice of the better model depends on the dependency structure of obligators and is crucial part of the modeling. The applied methods in previous studies include Pearson's correlation coefficient [1][2][3][4][5][6], Spearman's correlation coefficient [7][8][9][10], Kendall's correlation coefficient [11][12][13][14], Sen's slope [15][16][17], cross-correlation function [18][19][20] and copula [21][22][23][24][25][26]. When we face with the relationship of two stationary time series, crosscorrelation function and copula are suggested.…”
Section: Introductionmentioning
confidence: 99%